Prognostic Value of Circulating Lipoprotein in Patients with Locoregionally Advanced Nasopharyngeal Carcinoma - Ji-Jin Yao; Xiao-Jun He; Wayne R. Lawrence; Wang-Jian Zhang; Jia Kou; Fan Zhang; Guan-Qun Zhou; Si-Yang Wang; Ying Sun (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Lipoproteins have been reported to be associated with prognosis in various cancers; however, the prognostic value of lipoproteins in patients with nasopharyngeal carcinoma (NPC) remains largely unknown. We aim to asses the role of circulating lipoproteins in locoregionally advanced NPC patients. Methods: Between October 2009 and August 2012, a total of 1,081 patients with stage III-IVB NPC were included in the analysis. Circulating high-density lipoprotein (HDL) and low-density lipoprotein (LDL) are the two key lipoproteins, which were measured at baseline. Receiver operating characteristic (ROC) curve analysis was used to evaluate different cut-off points for lipoproteins. Actuarial rates were performed using Kaplan–Meier methods and the log-rank test. Results: The cutoff points of HDL, LDL, and LDL/HDL ratio were 1.17 mmol/L, 3.75 mmol/L, and 2.73, respectively. At 5 years, high HDL (> 1.17 mmol/L) was significantly associated with better overall survival (OS, 86.6% vs. 78.9%; P=0.004), distant metastasis-free survival (DMFS, 86.9% vs. 80.8%; P=0.004), locoregional relapse-free survival (LRFS, 90.8% vs. 85.4%; P=0.010), and progression-free survival (PFS, 79.1% vs. 70.2%; P= 0.001) than low HDL (≤1.17 mmol/L). In contrast, high LDL (> 3.75 mmol/L) tend to be inferior OS (79.1% vs. 84.9%; P= 0.016) in compassion with low LDL (≤3.75 mmol/L). Likewise, patients with high LDL/HDL ratio (> 2.73) tend to be inferior OS (79.3% vs. 86.9%; P=0.001), DMFS (81.9% vs. 86.5%; P=0.030), and PFS (72.6% vs. 77.8%; P= 0.034) than those of low LDL/HDL ratio (≤2.73). In multivariate analysis, baseline HDL was found to be a significant prognostic factor for LRFS (HR= 0.65; 95% CI, 0.45-0.93; P= 0.019) and PFS (HR=0.75; 95% CI, 0.58-0.98; P= 0.034). Conclusions: Circulating HDL is significantly associated with treatment outcomes in patients with locoregionally advanced NPC. We suggest that HDL measurements will be of great clinical significance in the management of NPC.